عقد إختيار القانون واجب التطبيق على العقد الدولي - العبودي, عباس زبون; علي, ليث عبد الرزاق (Journal of Legal Sciences, 2019)
The defferenation of the contract, as alegal concept, is one of the new ideas in scientific research, aim to charectrise each condition or obligation of the contract, as an independent contract of the other parts, conclude under the agreement of the parties on a specific object with its own cause; this idea had applied in international contract too, specifically with the choice of law applicable to the international contract, that’s also supported by the potentiality of chossing the applicable law after concluding the international contract.     The choice of the applicable law, play a significant role in implementing the function of the international contract as a gear to organize the legal relationship between parties with different nationalites or where the contract belong to defferent legal invironemnt with its object or effects.          Certainly, determine the applicable law to an international contract will insure the good relationship between its parties, and provide a referrance to specify the obligation of the parties; it does also will assist the court of the arbitaration tribunal to decide a conflict between the parties.